Totally Toxic Poisoned Wetlands - Honor Head (India Little Prodigy, 2023)
Earth's wetlands are crucially important land areas that can easily get overlooked when talking about bodies of water. Wetlands hold some of the most concentrated biodiversity of any ecosystem and act as a filter to help keep our water clean. This book explores the danger facing our wetlands, and what is at stake if we do not reverse the damage. The final spread gives readers the chance to conduct their own environmental investigation with guidelines on how to observe, monitor, and analyze the health of a wetland area. This volume introduces an important part of our ecosystem to the reader's attention and inspires scientists of all levels to take action.
Keywords: Sharing The Planet -- -Biodiversity